2006
DOI: 10.1093/heapol/czl020
|View full text |Cite
|
Sign up to set email alerts
|

The social shaping of childhood vaccination practice in rural and urban Gambia

Abstract: Improving childhood vaccination coverage is a key health policy objective in Africa, and as availability increases, it will depend on addressing issues of demand and timely schedule completion. This paper explores vaccination demand in urban and rural areas of The Gambia as shaped by prevailing local vaccination cultures (comprising maternal knowledge and understandings, socio-cultural contexts and interactions with health providers). A survey of 1,600 mothers constructed on the basis of prior ethnography find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 11 publications
3
53
1
3
Order By: Relevance
“…Variables such as parental education [4,[17][18][19][20][21][22][23], mothers' age [18,19], household income or wealth [4,11,17,19,22,24], family size or mothers' parity [4,[17][18][19], religion of caregivers [25,26], and location of labor and delivery [23] are well documented as correlates with the vaccination status of a child. We are only aware of four published studies conducted in SSA in the past 15 years that assessed KATCI [18,[27][28][29]. Only one of these studies analyzed how maternal attitudes towards immunizations correlate with the vaccination status of a child by undergoing a limited bivariate analysis of mother's negative attitudes towards local healthcare facilities providing vaccinations and child's measles vaccination status [18].…”
Section: Discussionmentioning
confidence: 99%
“…Variables such as parental education [4,[17][18][19][20][21][22][23], mothers' age [18,19], household income or wealth [4,11,17,19,22,24], family size or mothers' parity [4,[17][18][19], religion of caregivers [25,26], and location of labor and delivery [23] are well documented as correlates with the vaccination status of a child. We are only aware of four published studies conducted in SSA in the past 15 years that assessed KATCI [18,[27][28][29]. Only one of these studies analyzed how maternal attitudes towards immunizations correlate with the vaccination status of a child by undergoing a limited bivariate analysis of mother's negative attitudes towards local healthcare facilities providing vaccinations and child's measles vaccination status [18].…”
Section: Discussionmentioning
confidence: 99%
“…A study in the Gambia equally suggests that witchcraft beliefs are not necessarily competing with vaccination campaigns. 31 Prevailing gender inequality may offer an explanation for this paradox. In many societies, women tend to be blamed for their children's illness.…”
Section: Discussionmentioning
confidence: 99%
“…27 In low-income countries, fears are also linked to suspicion that vaccines are sometimes expired and may then become dangerous for a child. 28 Costs and accessibility problems are other important barriers to vaccination in low-income settings, [29][30][31][32][33] and gender inequality plays a major role in health-related decisionmaking. 34,35 A low maternal education also negatively influences immunization status of children.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Findings from these studies have played key roles in informing policy discourses, especially those relating to investment in education and health. 5,6 The potential societal benefits realized by investing in women's education are best described through the indirect benefits that educated mothers enjoy as the socioeconomic status of their household improves.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Gambia reported that peer influence among mothers in rural areas was important in their use of antenatal care services. 3 Maternal education has the potential to help mothers organize themselves and advocate for their children's health including voicing support for various malaria control programs like subsidize or free ITNs. In rural Tanzania, social marketing was, at one time, a bedrock strategy for bed-net distribution.…”
Section: Introductionmentioning
confidence: 99%